Validity and reliability of a new low-cost linear position transducer to measure mean propulsive velocity: The ADR device - Lopez-Torres, O.; Fernandez-Elias, V. E.; Li, J.; Gomez-Ruano, M. A.; Guadalupe-Grau, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Many sports and recreational strength training coaches consider movement velocity essential to improve performance, and velocity-based training has gained attention over the past decade. Furthermore, there is a lack of low-cost, easy to use, and reliable methods to measure movement velocity. Therefore, this current research aims to analyze the validity and reliability of a new linear position transducer device (ADR) for the measurement of barbell mean propulsive velocity. Seventeen trained participants (n = 14 men; n = 3 women; 21.2 ± 4.0 years) performed an incremental bench press exercise test against five different loads (45%, 55%, 65%, 75%, and 85% 1RM) at maximal concentric velocity. Barbell displacement was derived simultaneously from three devices including: a linear velocity transducer (T-Force, criterion measurement) and two linear position transducers (ADR and Speed4lifts (S4L)). The ADR mean propulsive velocity measurements demonstrated substantial validity compared to both T-Force and S4L at all loads (between the r values and p values r = .86-.99 p < 0.001). The ADR device was reliable showing very high Intraclass correlation coefficients (ICC (95% CI): 0.95 (0.90-0.98), 0.96 (0.91-0.98), 0.75 (0.55-0.88), 0.91 (0.83-0.93), 0.85 (0.72-0.93) for 45%, 55%, 65%, 75%, and 85% 1RM, respectively); low coefficients of variation (CV (95% CI): 9.93 (7.93-11.93, 11.25 (9.25-13.25), 6.78 (4.78-8.78), 10.95 (8.95-12.95), 14.40 (12.40-16.40) for 45%, 55%, 65%, 75%, and 85% 1RM, respectively), and small standardized typical error values (STE = 0.2-0.6). In conclusion, the ADR device can be considered an affordable, reliable, and valid method to measure movement velocity, thereby making it a practical resource for coaches when assessing velocity-based training at gyms.